Volatility of World Oil Prices Towards Venezuela's Economic Crisis - Achmad, Achmad (Kybernology : Journal of Government Studies, 2023)
The drop in world oil prices, especially in 2014, caused Venezuela to experience a crisis. This is because oil is the country's main commodity and 95% of Venezuela's exports come from oil commodities. This study uses a qualitative descriptive research method. By using the theory of International Political Economy, International Organization, and Price Liberalization, the author tries to find out the causes of the decline in world oil prices and efforts to stabilize world oil prices in this case OPEC and market mechanisms. The results of this study indicate that Venezuela's financial inability to deal with falling oil prices due to inappropriate government policies such as the Venezuelan Social Program has caused Venezuela to experience an economic crisis. This then causes further impacts in the form of a humanitarian crisis, namely poverty, hunger, unemployment, crime, and an increase in the number of Venezuelan refugees. The series of crises resulted in Venezuela becoming one of the countries that failed to overcome domestic crises.